2001
DOI: 10.1097/00003446-200110000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Some Measures of Verbal and Spatial Working Memory in Eight- and Nine-Year-Old Hearing-Impaired Children with Cochlear Implants

Abstract: Objective-The purpose of this study was to examine working memory for sequences of auditory and visual stimuli in prelingually deafened pediatric cochlear implant users with at least 4 yr of device experience.Design-Two groups of 8-and 9-yr-old children, 45 normal-hearing and 45 hearing-impaired users of cochlear implants, completed a novel working memory task requiring memory for sequences of either visual-spatial cues or visual-spatial cues paired with auditory signals. In each sequence, colored response but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
8
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 38 publications
8
94
8
10
Order By: Relevance
“…These children have been shown to have impaired immediate recall for sequences of stimuli regardless of modality of presentation provided that the stimuli can be verbally encoded (Cleary, Pisoni, & Geers, 2001;Dawson, Busby, McKay, & Clark, 2002;Pisoni & Cleary, 2003). Compared with normal-hearing children, prelingually deaf children with cochlear implants also display reduced immediate memory spans for auditory presentation of numbers, visual presentation of presentation of colored lights, auditory presentation of color names, and for auditory color names and lights presented together (Cleary et al, Pisoni & Cleary).…”
Section: Discussionmentioning
confidence: 99%
“…These children have been shown to have impaired immediate recall for sequences of stimuli regardless of modality of presentation provided that the stimuli can be verbally encoded (Cleary, Pisoni, & Geers, 2001;Dawson, Busby, McKay, & Clark, 2002;Pisoni & Cleary, 2003). Compared with normal-hearing children, prelingually deaf children with cochlear implants also display reduced immediate memory spans for auditory presentation of numbers, visual presentation of presentation of colored lights, auditory presentation of color names, and for auditory color names and lights presented together (Cleary et al, Pisoni & Cleary).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that verbal WM plays an important role in speech and language outcomes for children with CIs (Dawson, Busby, McKay, & Clark, 2002;Pisoni, 2014). Pediatric CI users consistently have poorer verbal WM than do age-matched NH peers, as determined through auditory tasks (Cleary, Pisoni, & Geers, 2001;Nittrouer et al, 2013). However, Dawson et al failed to find significant differences between children with NH and children with CIs in tasks of visuospatial WM, where the test items were unlikely to be recoded into verbal form.…”
Section: Wm Hearing Loss and Speech Recognitionmentioning
confidence: 99%
“…In a study from our laboratory, Cleary, Pisoni, and Geers (2001) reported that deaf children using cochlear implants had significantly shorter working memory spans for both verbal and spatial patterns than normal-hearing children. Other studies have found that pediatric cochlear implant users have shorter forward and backward digit spans than normal-hearing children Pisoni & Cleary, 2003).…”
Section: Introductionmentioning
confidence: 98%